1998
DOI: 10.1056/nejm199804233381702
|View full text |Cite
|
Sign up to set email alerts
|

Topical Treatment with Nerve Growth Factor for Corneal Neurotrophic Ulcers

Abstract: In this preliminary, uncontrolled study, topically applied exogenous nerve growth factor restored corneal integrity in patients with corneal neurotrophic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
226
0
11

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 367 publications
(242 citation statements)
references
References 29 publications
5
226
0
11
Order By: Relevance
“…Intracerebral administration of NGF has been shown to be beneficial in Parkinson's and Alzheimer's patients (10)(11)(12), and intraocular administration of NGF in animal models has been shown to inhibit RGC degeneration after mechanical, ischemic or hypertensive injury (13)(14)(15). NGF applied topically to the eye has also been shown to restore sensory nerve function to the ocular surface of patients with neurotrophic keratitis (16). Interestingly, absorption studies have demonstrated that topical ocular NGF reaches the retina, optic nerve, and brain in animals (17,18).…”
mentioning
confidence: 99%
“…Intracerebral administration of NGF has been shown to be beneficial in Parkinson's and Alzheimer's patients (10)(11)(12), and intraocular administration of NGF in animal models has been shown to inhibit RGC degeneration after mechanical, ischemic or hypertensive injury (13)(14)(15). NGF applied topically to the eye has also been shown to restore sensory nerve function to the ocular surface of patients with neurotrophic keratitis (16). Interestingly, absorption studies have demonstrated that topical ocular NGF reaches the retina, optic nerve, and brain in animals (17,18).…”
mentioning
confidence: 99%
“…52,53 In an open uncontrolled study, topical nerve growth factor NGF treatment induced corneal healing in 43 patients affected by moderate and severe neurotrophic keratitis (stages 2 and 3). 19,20 Restoration of corneal integrity was associated with recovery of corneal sensitivity in most of the patients. Topical treatment with NGF represents a promising therapy to prevent the onset and progression of neurotrophic keratitis.…”
Section: Future Developments and Conclusionmentioning
confidence: 97%
“…18 We have recently evaluated the potential role of nerve growth factor (NGF) in the treatment of neurotrophic keratitis. 19,20 NGF induces in vitro and in vivo recovery of sensory neurons and induces the production of Ach in the central nervous system and SP in the peripheral nervous system. 21,22 In addition, NGF plays an important role in the balance between sensory and sympathetic innervation, by modulating their functions.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several therapeutic strategies for delivery of NGF in animal models and in human diseases have been explored and clinical steps have been attempted, while others are currently in progress to evaluate whether NGF and/or TrkA receptor agonists can prevent or protect against cell degeneration in the nervous system, visual system, cutaneous and myocardial tissue (14,15,19,(22)(23)(24)(25)(26)(27)(28). It most likely exerts therapeutic effects on cardiometabolic diseases such as atherosclerosis, obesity, type 2 diabetes and metabolic syndrome (29)(30)(31).…”
Section: Ngf-ome or The Multiple Life Of Ngfmentioning
confidence: 99%